Intertextuality in the series Bolivar, an admirable struggle and the book Bolivar, liberator and enemy number 1 of Peru - Castillo-Hilario, Mario Buenaventura (2020)
The objective of this research was to identify the intertextual relationships between the television series Bolivar, an admirable struggle and the written biography Bolivar, liberator and enemy number 1 of Peru. For this, a qualitative approach and an interpretive design were chosen. Texts were read and interpreted to identify intertextual relationships in them. The following intertextual relationships were found: citations and allusions. There are similarities in Simon Bolivar's global presentation in relation to Peru; the battle of Pichincha; the entrance of Bolivar to the cities; the situations prior and the meeting in Guayaquil between Simon Bolivar and San Martin; the previous events and Bolivar's arrival in Peru; the battles of Junin and Ayacucho; the lifetime Constitution; and the last days of Bolivar in Peru and his departure. The series reaffirms the idea that the independence of Peru was "granted”.